Examining The Vocational School Teacher Made Tests For School Final Examination In Enrekang - Saud, Chaerul Fadlan; Saud, Syukur (Academic : Journal of Social and Educational Studies, 2025)
Abstract. This paper reports the result of a research that aimed at finding out the procedures that the teachers in vocational schools in Enrekang follow in constructing teacher-made tests for school final examination at the even semester in 2024/ 2025. The quality of those teacher-made tests was also analyzed according to its item analysis. This research employed survey research using descriptive method. By applying simple random sampling, there were five out of eight vocational schools selected as samples. The results of analysis showed preparation that senior high school teachers follow in constructing teacher-made tests in Enrekang is divided into three main parts. . In preparing test specification for the test, the procedures were considering tests’ materials and proportion of each topic and choosing the test items from the item bank that match to syllabus and indicators. In writing test, teachers’ procedures were re-writing chosen test item from item bank which based on indicators, combining items from item bank and students’ text book, writing key answers of the test, deciding the proportion of test items from grade X, XI and XII, and considering test difficulty. While in analyzing the test, the procedures used by the teachers were analyzing the test based on the students’ ability, making distractors and considering the difficulty level of the tests, pretesting, and revising the test before administering it for UAS. Moreover, the item analysis showed that the percentage of revised items is bigger than the percentage of used items. The biggest failures of those UAS tests made by the teachers are in terms of validity and discrimination indexKeywords: teacher made tests, test quality, validity, reliability, difficulty level, discrimination index, distraction power